Plasma guns of an erosion type with the pulse-periodic gas-metal injection - Vinnikov, D.V.; Katrechko, V.V.; Yuferov, V.B.; Tkachev, V.I. (Problems of Atomic Science and Technology, 2022)
The design of the modular plasma guns of an erosion type that operate in the pulse-periodic mode has been described. The injection of the electrode and dielectric materials occurs due to the combination of many processes initiated by the high-voltage surface discharge. The guns with the dielectrics of (C₂H₄)n and (C₂F₄)n types have been compared. Optical spectrograms of discharges for a (C₂F₄)n dielectric have been obtained. The radial and axial spread of sprayed components that are the part of plasma guns has been specified and the composition of the sediments deposited on the targets has been defined. Описано влаштування плазмових гармат ерозійного типу модульної конструкції, що працюють у імпульсно-періодичному режимі. Інжекція матеріалу електродів та діелектрика відбуваються за рахунок комплексу процесів при високовольтному поверхневому розряді. Проведено порівняння гармат з діелектриками (C₂H₄)n- та (C₂F₄)n-типу. Отримано оптичні спектрограми розрядів для (C₂F₄)n-діелектрика. Визначено радіальний та осьовий розліт розпилених компонентів, що входять до складу плазмових гармат. Визначено склад осаду на мішені.